Egypt's energy reserves, and the role of the EU on a potential Egypt-Israeli energy cooperation - Ασβεστόπουλος, Εμμανουήλ (Πανεπιστήμιο Πελοποννήσου, 2018)
Τhe dissertation examines the energy outlooks and the ensuing challenges for Egypt, Israel and the European Union The deterioration of EU relations with Russia and the recent gas discoveries in Eastern Mediterranean took place almost simultaneously. Each development has had a different implication on EU’s energy policy. The tensions with Russia was the mobilizing force for the European policymakers to reduce the Union’s dependence from Russian gas, while the new gas findings in Eastern Mediterranean can help EU to achieve a higher level of energy security. This dissertation assesses these new gas findings, in relation to the regional environment. Three possible options for gas transportation are captured, with the drawbacks and advantages of each one being examined thoroughly. My research suggests the transportation of gas to EU to be conducted through Egyptian LNG plants.
Τα ενεργειακά αποθέματα της Αιγύπτου και ο ρόλος της Ευρωπαϊκής Ένωσης σε ενδεχόμενη ενεργειακή συνεργασία Αιγύπτου-Ισραήλ
Keywords: Ενεργειακοί πόροι; Φυσικοί πόροι; Ενέργεια; Ασφάλεια, Διεθνής; Μεσόγειος, Περιοχή της; Φυσικό αέριο; Ανατολική Μεσόγειος; Ενεργειακή ασφάλεια; Ισραήλ; Ευρωπαϊκή Ένωση